Mothering role of rural-urban Filipino migrant women employed in domestic work - de Guzman, Julie Kristine A.; Roldan, Aurorita T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This is a qualitative study on the perceptions, performance, and challenges and strategies related to the mothering role of rural-urban Filipino migrant women employed in domestic work. Data were gathered using semi-structured in-depth interview with 30 respondents selected through purposive-snowball sampling. The target population were migrant women in selected urban areas in Luzon from any rural area in Visayas and Mindanao; with at least one biological child left in Visayas or Mindanao; in a paid and stay-in domestic work setup for an employer/s who was/were not their biological relative/s; and with at least a year of employment. Regardless of marital status, sampled mothers perceived and performed the mother role as a provider. Children's education was the topmost priority and reason for migration. Most of them had young to adolescent children being taken cared by kin. Results revealed that sadness due to distant mothering was a major challenge to them. Their perceived traditional nurturer role was pertinent to their performance, challenges and strategies. This was generally renegotiated by technology-mediated communication, gift delivery, and occasional visits. Results suggested that the mothers perceived themselves and performed as both "haligi and ilaw ng tahanan" (pillar and light of the home). Their experiences illustrated the apparent redefinition and renegotiation of the traditional mothering role. Accepting their social reality and making adjustments were the most common strategies. Most of them perceived either satisfaction or extreme satisfaction with their mothering role performance despite sadness as a major challenge. Marital status, family structure, and age of children seemed to be influential to their experiences. Further studies using mixed-approach of quantitative and qualitative is recommended to explore relationship of migrant women with their own mothers and possible programs that would provide more options for rural women to work in their own locale.
Thesis (Master of Family Life and Child Development)--University of the Philippines Diliman
Keywords: Working mothers -- Family relationships -- Philippines; Children of working mothers -- Philippines; Women household employees -- Philippines; Work-life balance -- Philippines